THE IMPORTANCE OF SOCIAL MEDIA IN THE PROMOTION AND DEVELOPMENT OF THE CREATIVE INDUSTRIES IN THE REPUBLIC OF SERBIAe Republic of Serbia - Vasić, Ivana; Gajić, Jelena (The European Journal of Applied Economics, 2024)
Creative industries are a key element of contemporary creativity and modern economies and have a great influence on various spheres of society. The COVID-19 pandemic has significantly accelerated the application of digital transformation by finding numerous innovative ways to consume creative and cultural content, thereby strengthening interconnectedness. Predictions at the global level indicate that in the coming years, there will be an intensive use of digital tools that will have a great impact and importance for promoting the content of the creative industry. Digital marketing will play a key role in attracting audiences and creating brands in the market. The main driving force behind the development of creative industries in many countries, including ours, will be digital transformation. The aim of the paper is to analyze different approaches to defining the creative industry sector and their impact on the economic and cultural development of the Republic of Serbia. A special contribution of this paper is the conducted research, the focus of which was to determine the perception of the citizens of our country about the existence and importance of creative industries, as well as the attitudes about the more intensive use of digital means of advertising in the mentioned sector. The results show that our citizens are not sufficiently familiar with the term industry and that one of the reasons for this is the lack of marketing activities, as well as the insufficient cooperation of economic and educational institutions in this area.
Keywords: creative industry, digital marketing, models of creative industry, Republic of Serbia, creative city.